Tuneable intramolecular intermetallic interactions as a new tool for programming linear heterometallic 4f-4f complexes - Dalla-Favera, Natalia; Hamacek, Josef; Borkovec, Michal; Jeannerat, Damien; Ercolani, Gianfranco; Piguet, Claude (Inorganic chemistry, 2007)
Statistical mechanics predicts that the design of pure organized heteropolymetallic chains of metal ions bound to linear receptors depends on controlled deviations from the mixing rule DeltaE(MiMj) = 1/2 (DeltaE(MiMi) + DeltaE(MjMj)), whereby DeltaE(MiMj) is the intramolecular intermetallic interaction between neighboring metal i and metal j along the receptor. A thorough investigation of linear polymetallic trivalent lanthanide triple-stranded helicates shows that such deviations are amplified by an increase in the nuclearity of the final complexes and are thus easily evidenced in the tetranuclear heterobimetallic helicates [La(4-y)Lu(y)(L6)3](12+) (y = 0-4). The chemical and physical origins of this unprecedented behavior are discussed together with its practical consequences for programming pure heteropolymetallic 4f-4f complexes.